2017
DOI: 10.1016/j.jml.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The multimodal nature of spoken word processing in the visual world: Testing the predictions of alternative models of multimodal integration

Abstract: a b s t r a c tAmbiguity in natural language is ubiquitous, yet spoken communication is effective due to integration of information carried in the speech signal with information available in the surrounding multimodal landscape. Language mediated visual attention requires visual and linguistic information integration and has thus been used to examine properties of the architecture supporting multimodal processing during spoken language comprehension. In this paper we test predictions generated by alternative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 66 publications
2
32
1
Order By: Relevance
“…These data indicated strong activation of the semantic properties of both the semantically related object and the spoken target word but little activation of the semantic properties of the visually related object, the phonologically related object and the unrelated object. This contrasts with simulations in Smith et al 27 using a fine-coding of the phonological input which showed early strong activation of the semantic properties of the phonological competitor. Fig.…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…These data indicated strong activation of the semantic properties of both the semantically related object and the spoken target word but little activation of the semantic properties of the visually related object, the phonologically related object and the unrelated object. This contrasts with simulations in Smith et al 27 using a fine-coding of the phonological input which showed early strong activation of the semantic properties of the phonological competitor. Fig.…”
Section: Resultscontrasting
confidence: 98%
“…After 750,000 trials, the effect was earlier, from time step 12, all |t| ≥ 2.513, all p ≤ .040, maximum ratio = 1.667, and after 1,000,000 trials, it continued to be significant from time step 12, all |t| ≥ 2.630, all p ≤ .034, with maximum ratio = 1.525. Interestingly, as for the simulations in Smith et al 27 using a fine-coding of the phonological input, the model demonstrated a prolonged effect of phonological relatedness, which was consistent with the developmental data, but not with adult performance for such visual world tasks. Furthermore, as in the developmental behavioural data, the phonological effect was substantially smaller than that of the semantic effect (as seen in Figure 2, panels B, C and D).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations